Physical Activity Among Persons Aging with Mobility Disabilities: Shaping a Research Agenda - Dori E. Rosenberg; Charles H. Bombardier; Jeanne M. Hoffman; Basia Belza (Journal of Aging Research)
With the aging of the baby boomer population and their accompanying burden of disease, future disability rates are expected to increase. This paper summarizes the state of the evidence regarding physical activity and aging for individuals with mobility disability and proposes a healthy aging research agenda for this population. Using a previously published framework, we present evidence in order to compile research recommendations in four areas focusing on older adults with mobility disability: (1) prevalence of physical activity, (2) health benefits of physical activity, (3) correlates of physical activity participation, and, (4) promising physical activity intervention strategies. Overall, findings show a dearth of research examining physical activity health benefits, correlates (demographic, psychological, social, and built environment), and interventions among persons aging with mobility disability. Further research is warranted.